Incidental testicular masses and the role of organ-sparing approach - Yash Narayan (Archivio Italiano di Urologia e Andrologia, 2021)
Objectives: The widespread use of ultrasonography for the investigation of common urological conditions, such as infertility or pain, has resulted in an increased incidence of incidental non-palpable testicular masses. The majority of these are expected to be benign therefore a conservative approach, either active monitoring or organsparing approach, is recommended. However, there are no clinical or radiological parameters which define the exact nature of such lesions and optimal patient selection criteria are lacking. In this comprehensive review we discuss the significance of incidental, small testicular masses (STMs) and the role of organ-sparing approach in the management of these lesions. Materials and methods: A non-systematic search was performed using PubMed to identify articles that covered the following topics; clinical implications at diagnosis, role of imaging in identifying the malignant capabilities of a lesion, role of surgery and the final pathology. Results: Incidental STMs are routinely identified following ultrasound examination of infertile men. STMs usually measure a few millimeters in size and the majority of these are benign. Therefore, strict follow up or an organ-sparing approach, with utilisation of frozen section analysis (FSA), is favored for STMs. FSA has a high correlation with final pathology and prevents unnecessary orchidectomies. Advances in imaging, namely ultrasound and magnetic resonance imaging may provide enhanced assessment of STMs and guidance intraoperatively. Conclusions: The optimal approach is not well defined and there is no specific clinical parameter that can predict the nature of STMs. The increasing incidence of small, benign testicular masses has resulted in the development of organ-sparing surgery to investigate and manage these lesions. Organ-sparing surgery has been shown to be practical and carries excellent oncological outcomes.